New asylum countries? : Migration control and refugee protection in an enlarged European Union. - Byrne, R. (BRILL, 2002)
How is access to asylum and other forms of extraterritorial protection regulated in the European Union? Is the EU in conformity with international law in this area? Which tools does international law offer to solve collisions between both? And, finally, is law capable of bridging the foundational oppositions embedded in migration and asylum issues?This volume discusses the transformation of asylum in Europe in the context of the EU enlargement process. This transformation involves norms, as well as the procedures and resources for their implementation. In the candidate countries, as in the wes.